2016
DOI: 10.1364/oe.24.020021
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry breaking induced excitations of dark plasmonic modes in multilayer graphene ribbons

Abstract: Multilayer graphene can support multiple plasmon bands. If structured into graphene ribbons, they can support multiple localized plasmonic modes with interesting optical properties. However, not all such plasmonic modes can be excited directly due to the constrains of the structural symmetry. We show by numerical simulations that by breaking the symmetry all plasmonic modes can be excited. We discuss the general principles and properties of two-layer graphene ribbons and then extend to multilayer graphene ribb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…For example, Zhang et al and Guo et al reported that different higher-order plasmon modes of patterned graphene acting as narrow modes interact with a broad dipolar mode to generate different higher-order FRs in pure graphene or hybrid graphene-metal metamaterials [27,32]. On the other hand, plasmon hybridization among neighboring graphene structures is an effective way to generate new narrow hybridized plasmon modes through optical near-field coupling [33][34][35]. A previous effort was focused on achieving the narrow electric dipole symmetric and antisymmetric modes by plasmon hybridization in a stacked graphene nanoribbon pair, and the formation mechanism of double FRs in a symmetrical structure of a graphene-metal metamaterial [36].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhang et al and Guo et al reported that different higher-order plasmon modes of patterned graphene acting as narrow modes interact with a broad dipolar mode to generate different higher-order FRs in pure graphene or hybrid graphene-metal metamaterials [27,32]. On the other hand, plasmon hybridization among neighboring graphene structures is an effective way to generate new narrow hybridized plasmon modes through optical near-field coupling [33][34][35]. A previous effort was focused on achieving the narrow electric dipole symmetric and antisymmetric modes by plasmon hybridization in a stacked graphene nanoribbon pair, and the formation mechanism of double FRs in a symmetrical structure of a graphene-metal metamaterial [36].…”
Section: Introductionmentioning
confidence: 99%
“…The method has been successfully applied to graphene sheets and ribbons. [11][12][13][14][15][16][17][18][19][20][21] To tune graphene plasmonic resonances, electrical gating has been dominantly used. [35,36] Moreover, intrinsic absorptions from either conducting substrates or ion gels are inevitable, which may degrade considerably graphene plasmonic resonances.…”
mentioning
confidence: 99%